PERMAINAN KATA DALAM ASTERIX - Pratiwi, Shinta Ayu; Junus, Fierenziana G; masdiana, masdiana (JURNAL ILMU BUDAYA, 2014)
This article aims to explain the function of humor by taking the Astérix comics as a data source. In a comic, thereare many elements of humor usually obtained through word or image games. And those elements will be analyzedand be explained through linguistic approach to determine the role the humor plays in a comic.This study uses semantic and phonology approach to analyze the data. The results showed that the type of wordgames with the highest frequency of occurrence is polysemy which are included in semantic theory. Based on thestudy, the function of word games is to add an element of humor that can make a person feel comforted. This isevidenced by the statement of the experts in linguistics that humor can be approach by semantics and pragmatics.Keyword : word games, humor, functions.